The Age of Empathy. Nature’s Lessons for a Kinder Society, by Fran de Waal - Milito Barone, Cecilia (Historia y Memoria de la Educación, 2015)
Review of the book The Age of Empathy. Nature’s Lessons for a Kinder Society. by Fran de Waal